Breast reconstruction: a review - Brito-Brito, Nicolás R.; Castro-Jadán, Christian B.; Gómez-Alvarado, Arturo; Berrazueta-Peñaherrera, Viviana E.; Ramírez-Miguel, Williams O.; Benítez Villacís, Paola A.; Zermeño-Torres, Jana; Baeza Ramos, José H.; Velasco Cabrera, José A.; Valderrama-Treviño, Alan Isaac; Barrera-Mera, Baltazar (International Journal of Research in Medical Sciences, 2023)
Surgeons in the late 19th - 20th century performed radical mastectomies as the only possible treatment for breast cancers. Since then, the medical-surgical/scientific community has been constantly encouraged to develop and study different less invasive alternatives in breast reconstruction. Over time, locoregional perforator flap options have served as practical alternatives to implant-based reconstruction and abdominal flaps, especially in the setting of patients who have received radiation therapy or have a history of failed reconstruction, as they effectively fill the missing volume and respect the musculature of the donor site. Breast reconstruction using strategies with one of the different locoregional flaps can preserve the musculature and innervation of the post-mastectomy site, which manages to reduce possible adverse events. In addition to evaluating the anatomical characteristics of the defect and affected quadrant, it is essential to assess the patient’s body constitution and the skills of the surgical team as well as microsurgery training when designing a reconstructive plan. Different research protocols should be developed in the study and development of new medical-surgical therapeutic alternatives; we suggest joint development with tissue engineering.